2023
DOI: 10.1002/aenm.202204304
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination and its Effects on Electrocatalysts for Low‐Temperature Fuel Cells

Abstract: The benefits of covalent grafting of fluorine atoms onto carbonaceous materials are described for the design of new electrocatalysts for low‐temperature fuel cells. In order to obtain the best results, the fluorination conditions must be carefully chosen according to the physicochemical properties of the starting materials (specific surface area, pore size distribution, crystallinity, and doping). By describing the main fluorination routes, the article aims to help in the choice of efficient treatment conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 177 publications
(303 reference statements)
0
7
0
Order By: Relevance
“…Notably, Hyun et al demonstrated that mitigating water imbalance through carbon modifications can help achieve stable operation for 1000 h, which is in contrast to the short lifetime (200 h) of the control MEA. 143 Various carbon modification methods including fluorination 11 can be used in this approach.…”
Section: Challenges and Solutions For Improving The Power Performance...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Hyun et al demonstrated that mitigating water imbalance through carbon modifications can help achieve stable operation for 1000 h, which is in contrast to the short lifetime (200 h) of the control MEA. 143 Various carbon modification methods including fluorination 11 can be used in this approach.…”
Section: Challenges and Solutions For Improving The Power Performance...mentioning
confidence: 99%
“…1b). Regarding the former, carbon modification technologies such as the fluorination of the carbon support surface 11 attract interest because of their critical role in minimizing water flooding on the anode side of AEMFCs. While Pt is mainly being used at the single-cell level, Ag, 12,13 Co, 14 Ni, 15 and Fe metals 16 or alloys 17,18 have been studied as catalysts for AEMFCs.…”
Section: Reviewmentioning
confidence: 99%
“…The development of low-temperature fuel cells is one of the effective strategies for achieving high-efficiency conversion of sustainable energy and low-/zero-carbon emissions. However, the cathodic oxygen reduction reaction (ORR), which shows sluggish reaction kinetics with multielectron reaction steps, always limits the power density of fuel cells. Pt-based nanomaterials have been regarded as state-of-the-art catalysts for accelerating ORR kinetics, while the scarcity and weak antitoxicity of Pt severely inhibit their large-scale applications. Notably, Pd shows a similar chemical property and electronic structure to Pt and is found to deliver relatively larger reserves and higher toxicity resistances, resulting in its emergence as an attractive Pt alternative toward ORR electrocatalysis. Unfortunately, the strong interactions between surface Pd sites and the oxygen-containing intermediates involving *O, *OH, and *OOH conventionally result in sluggish ORR electrocatalytic processes. Although extensive explorations have been devoted so far to accelerating the ORR kinetics of Pd-based nanomaterials, their activities and stabilities are still far from expected. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, thermal treatment can enhance the stability and durability of electrocatalysts, making them more resistant to degradation mechanisms such as corrosion and agglomeration, and enabling longterm performance under harsh operating conditions. [8][9] This review article has an objective to offer a comprehensive exploration of the impact of thermal treatment on enhanced electrocatalysis. A deep dive into the fundamentals of thermal treatment techniques and their effects on electrocatalytic materials is taken, with the intent to elucidate the underlying mechanisms and highlight the achievable benefits.…”
Section: Introductionmentioning
confidence: 99%
“…These modifications can lead to improved catalytic activity, enhanced reaction kinetics, reduced overpotential, and lower energy consumption. Additionally, thermal treatment can enhance the stability and durability of electrocatalysts, making them more resistant to degradation mechanisms such as corrosion and agglomeration, and enabling long‐term performance under harsh operating conditions [8–9] …”
Section: Introductionmentioning
confidence: 99%